PERAN SIFAT TANAH AWAL DALAM PERUBAHAN SIFAT KIMIA TANAH SULFAT MASAM AKIBAT APLIKASI JERAMI PADI - s, Nurzakiah; A, Fahmi (AgriPeat, 2020)
Tidal land is a swamp land which directly or indirectly affected by sea water tides. The overflow and intensity of tides or fluctuation of ground water levels strongly influence to the soil properties. This review is constructed to examine the role of native soil properties towards the changes in chemical properties of acid sulphate soils that occured due to organic matter application. This paper is a review of the data in the paper "Changes of soil chemical properties during rice straw decomposition in different types of acid sulphate soil", published by Hairani and Susilawati in Tropical Soil Journal ( 2013), those data reviewed with different perspectives and theories. Changes in soil pH, Fe and P concentrations due to the application of organic matter are not only influenced by differences in buffering capacity and reduction capacity of the two types of soil but are also influenced by the original soil pH, high cellulose content in straw, soil development and soil hydrological conditions, and Fe2+ content